Preparation of TiNbTaZrMo high-entropy alloy with tunable Young's modulus by selective laser melting. (6th January 2023) - Feng, Junyi; Wei, Daixiu; Zhang, Peilei; Yu, Zhishui; Liu, Changxi; Lu, Weijie; Wang, Kuaishe; Yan, Hua; Zhang, Laichang; Wang, Liqiang
Abstract: Biological high-entropy alloy (Bio-HEA) is a new generation of biomedical alloys with excellent mechanical properties and good biocompatibility. However, elemental segregation often exists during conventional casting or arc melting, which dramatically degrades their mechanical performance. Here, we utilized the selective laser melting (SLM) technique to fabricate dense blocks with low Young's modulus and good compression property at room temperature. Then, we fabricated HEA with triply periodic minimal surface (TPMS) lattice, which has Young's modulus (6.71–16.21 GPa) very close to that of human trabecular bone. This structure provides the possibility of meeting the requirement of various bone implants by customizing the shape and porosity of the TPMS lattice, affirming the possibility of Bio-HEA for biomedical applications. Graphical abstract: Unlabelled Image